A Developer Relations (DevRel) model to govern developers in Software Ecosystems. Issue 5 (12th October 2021) - Fontão, Awdren; Cleger‐Tamayo, Sergio; Wiese, Igor; Pereira dos Santos, Rodrigo; Claudio Dias‐Neto, Arilo
Abstract: Software Ecosystem (SECO) comprises third‐party developers cooperating and competing when contributing to a platform provided by a central organization (keystone). There are keystones investing in Developer Relations (DevRel) internal team as a global business strategy to attract and engage a critical mass of third‐party developers in producing and evolving contributions. For this reason, the DevRel team should promote social relationships among SECO actors and synergy among keystone' goals and developers' expectations to survive to inherit changes. However, the understanding of DevRel structure and the way DevRel team can act on a SECO to better engage the developers' communities establishing a robust VCN (Value Creation Network) remain a challenge. In this article, we advance on the structure for developers' governance from DevRel by proposing and refining a model because of the following research methods: grey literature review, opinion survey, and interviews. The model is called DevGo (DEVeloper GOVernance) and consists of four focus areas, three developer advancement phases, six stages, enablers, and value transfer objects. In addition, a set of 62 lessons learned from DevRel practitioners is associated with DevGo stages. Abstract : We advance on the structure for developers' governance from DevRel by proposing and refining a model because of the following research methods: grey literature review, opinion survey and interviews. The model is called DevGo (DEVeloper GOVernance) and consists of four areas, three developer advancement phases. In addition, a set of 62 lessons learned from DevRel practitioners is associated with DevGo stages.